Program Manajamen Pendidikan Dan Pelatihan (Diklat) Dalam Upaya Meningkatkan Kinerja Guru - Ahmad Rinaldi Siregar; M Muflih Dermawan; Fachri Habib; Abdul Fattah Nasution (CV. ITTC INDONESIA, 2024)
This research was conducted to answer how education and training management programs (training) can improve teacher performance. The type of research used is library research or literature study, where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. Training Management is a systematic and planned effort to optimize all training components in order to achieve program objectives effectively and efficiently. Programs carried out to improve teacher performance can take the form of mastering technology and information, developing creativity, developing learning methods and developing innovation.